Baseline T Classification Predicts Early Tumor Regrowth After Nonoperative Management in Distal Rectal Cancer After Extended Neoadjuvant Chemoradiation and Initial Complete Clinical Response. Issue 6 (June 2017) - Habr-Gama, Angelita; São Julião, Guilherme Pagin; Gama-Rodrigues, Joaquim; Vailati, Bruna Borba; Ortega, Cinthia; Fernandez, Laura Melina; Araújo, Sérgio Eduardo Alonso; Perez, Rodrigo Oliva
Abstract : BACKGROUND: Selected patients with rectal cancer and complete clinical response after neoadjuvant chemoradiation have been managed nonoperatively with acceptable outcomes. However, ≈20% of these patients will develop early tumor regrowth. Identification of these patients could select candidates for more intensive follow-up. OBJECTIVE: The purpose of this study was to investigate the influence of baseline radiological T classification on recurrences after a complete clinical response managed nonoperatively after chemoradiation. DESIGN: This was a retrospective review of a prospective collected database. SETTINGS: The study was conducted at a single center. PATIENTS: Patients with distal rectal cancer (cT2-4N0-2M0) undergoing extended chemoradiation (54 Gy + 5-fluorouracil–based chemotherapy) were eligible. Patients were reassessed for tumor response at 10 weeks after radiation completion. Patients with complete clinical response (clinical, radiological, and endoscopic) were managed nonoperatively and strictly followed. MAIN OUTCOMES MEASURES: Complete clinical response rates, early tumor regrowth rates (<12 mo), local recurrence-free survival, and distant metastases-free survival were measured. RESULTS: A total of 91 consecutive patients with rectal cancer underwent extended chemoradiation. Sixty-one patients developed initial complete clinical response (67%). cT2 patients developed similar initial complete clinical response rates compared with cT3/T4 (72% vs 63%; p = 0.403). Early tumor regrowths were more frequent among baseline cT3/4 when compared with cT2 patients (30% vs 3%; p = 0.007). There were no differences in late local recurrences ( p = 0.593) or systemic recurrences ( p = 0.387). Local recurrence-free survival was significantly better for cT2 patients at 1 year (96% vs 69%; p = 0.009). After Cox regression analysis, baseline T stage was an independent predictor of improved local recurrence-free survival at 1 year ( p = 0.03; OR = 0.09 (95% CI, 0.01–0.81)). LIMITATIONS: This study was limited by its small sample size, retrospective nature, and short follow-up. CONCLUSIONS: cT2 patients who develop complete clinical response after extended chemoradiation managed nonoperatively are less likely to develop early tumor regrowths when compared with cT3/4 patients. cT3/4 patients should undergo more intensive follow-up after a complete clinical response to allow for early detection of early regrowths.